IoT Sea Level Monitoring Development and Field Testing Study - Hollanda Kusuma; Muhammad Aris Akbar; Tonny Suhendra; Achmad Zuchriadi; Allsay Kitsash Addifisyukha Cintra (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2023)
The measurement of sea level is essential to oceanography because it provides vital information about the ocean environment, such as tides, currents, and water temperature. This research aimed to develop an Internet of Things (IoT)-based sea level monitoring device that can precisely measure sea level and transmit data in real time. An ESP32 microcontroller, a GSM module, an MS5803-14BA sensor, and a battery constituted the device. To protect the electronics from the ocean environment, the components were assembled on a PCB board and placed within a waterproof box. The field test was conducted for 17 hours at the Class 1 Navigation Office Port in Tanjungpinang, and the Ubidots platform was used to monitor the data. The device accurately measured sea level with an RMSE of 0.69 cm and an accuracy rate of 99.47%, according to the results. However, the field test also revealed problems with data transmission, with 18.81% of the data not being transmitted to the server. This low data transmission rate may have been caused by low RSSI levels and signal quality issues with the operator. To understand the causes of these data losses and improve the device's overall performance, additional research is required. This study demonstrated the viability of utilizing an Internet of Things-based sea level monitoring device to precisely measure sea level and transmit data in real time. It provides valuable information for the improvement and further development of sea level monitoring systems.